2010
DOI: 10.1308/003588410x12628812458257
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adequacy of procedure-specific consent forms in orthopaedic surgery against current methods of operative consent

Abstract: Providing patients with an Orthoconsent form significantly improves knowledge of their planned procedure as well as constituting a more robust means of information provision and consent documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Several alternatives to the typical consent form and process have been suggested in the literature. Barritt et al [17] reported that procedure-specific consent forms were superior to generic consent forms for both knee arthroscopy and total knee replacement for patient understanding. Finch et al [18] conducted a randomised control trial for consent for transurethral resection of prostate, comparing the conventional consent against procedure-specific consent forms produced by the British Association of Urological Surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Several alternatives to the typical consent form and process have been suggested in the literature. Barritt et al [17] reported that procedure-specific consent forms were superior to generic consent forms for both knee arthroscopy and total knee replacement for patient understanding. Finch et al [18] conducted a randomised control trial for consent for transurethral resection of prostate, comparing the conventional consent against procedure-specific consent forms produced by the British Association of Urological Surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of procedure‐specific consent forms have been assessed by orthopaedic surgeons as well. Barritt et al . reported that by using procedure‐specific consent forms for knee arthroscopy and total knee replacement, the level of patients' understanding was significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…One method to improve these is to convey standardised information using procedure specific consent forms 19 . This approach has been reported to improve recall rates in patients undergoing knee arthroscopy and arthroplasty 20 . The variability of the information recorded on ordinary consent forms by junior staff lends support to the use of such printed and standardised consent forms 12,20,21 .…”
Section: Discussionmentioning
confidence: 99%